Relationship of Parathyroid Hormone Levels with Uremic Neuropathy in Chronic Kidney Disease Patients - Rizki Muhammad Rananda; Yuliarni Syafrita; Restu Susanti (HM Publisher, 2022)
Background: Parathyroid hormone is known as one of the main uremic toxicants, which, if the amount increases in plasma, will affect motor conduction in patients with chronic kidney disease. This study aims to determine the relationship between Parathyroid hormone levels with uremic neuropathy in patients with chronic kidney disease. Methods: This study was an analytic observational study with a cross-sectional approach, where as many as 42 subjects participated in this study. Data analysis was performed using SPSS using univariate and bivariate, with p<0.05. Results: There was a difference in the average thyroid hormone levels in neuropathy and without neuropathy, but statistically, it was not different p>0.05. Conclusion: There is no relationship between parathyroid hormone and uremic neuropathy in patients with chronic kidney disease.